2014
DOI: 10.1002/aenm.201400252
|View full text |Cite
|
Sign up to set email alerts
|

Surface Generation of a Cobalt‐Derived Water Oxidation Electrocatalyst Developed in a Neutral HCO3/CO2 System

Abstract: near-neutral pH (pH = 6.7-6.8), the cobalt-bicarbonate-derived electrocatalyst (Co-Ci) is readily generated on conducting oxide electrode surfaces such as FTO (fl uorine-doped tin oxide) and ITO (indium tin oxide), or on a glassy carbon (GC) anode and show remarkable activity for water oxidation during extended period operation (Figure 1 ). At 1.37 V (vs NHE) in a HCO 3 − / CO 2 system at near-neutral pH, a stable oxygen evolution current density ( J ) of ≈2.0 mA cm −2 was obtained during constantpotential ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 32 publications
2
79
2
Order By: Relevance
“…The BiVO 4 /WO 3 shows predominant M-O peak at 529.3 eV with a very small peak at 531 eV (Figures S5b and 2c). The trend is reversed in Co-Ci/ BiVO 4 /WO 3 (Figures S6b and 2d), which showed a small M-O peak and a large non-metal oxide peak at 531 eV [25,30]. Surface elemental composition by XPS in Table S1 showed increase in C, decrease in O, and a large decrease in Bi and V after Co-Ci deposition.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The BiVO 4 /WO 3 shows predominant M-O peak at 529.3 eV with a very small peak at 531 eV (Figures S5b and 2c). The trend is reversed in Co-Ci/ BiVO 4 /WO 3 (Figures S6b and 2d), which showed a small M-O peak and a large non-metal oxide peak at 531 eV [25,30]. Surface elemental composition by XPS in Table S1 showed increase in C, decrease in O, and a large decrease in Bi and V after Co-Ci deposition.…”
Section: Resultsmentioning
confidence: 71%
“…BiVO 4 /WO 3 predominantly showed C-C peak from contaminated carbon with a small peak at 284.6.0 eV ( Figure S5). However, increase in intensity of C 1s peak and stronger 288.0 eV peak upon Co-Ci deposition indicate the presence of a CO 3 2 À -like species (Figures 2b,c and S5) [25,30]. More obvious indication of the carbonate species in Co-Ci/BiVO 4 / WO 3 could be observed from the O 1s spectrum, which gave peaks at 529.3 eV assigned to M-O and at 531 eV assigned to -CO x and surface -O-H groups.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Joya et al [53] reported the use of a cobalt carbonate (Co-Ci) OEC produced in situ, generated from a CO 2 saturated bicarbonate solution containing Co 2+ ions. They reported that the Co-Ci OEC in a HCO 3 − /CO 2 electrolyte showed a stable current density of >2 mA/cm 2 at 1.35 V vs. NHE (normal hydrogen electrode), and remained active for 16 h. It was also reported that Co-based OECs, such as Co-Pi and Co-Ci, tend to lose stability in a phosphate electrolyte system during anodic water oxidation, although, they also exhibit a sustained current density and higher stability in a HCO 3 − /CO 2 system.…”
Section: Strategies Adopted To Enhance Reaction Kinetics In Solar Watmentioning
confidence: 99%
“…This oxygen evolution onset potential and catalytic current density of the silver-oxide based electrocatalyst are comparable to those observed for Ni-oxide and Co-oxide based materials generated electrochemically in near-neutral conditions. [17,27] RuO 2 and IrO 2 are the benchmark materials for water oxidation in acidic condition. The catalytic activity data for AgOx-NP and RuO 2 and IrO 2 in near-neutral borate buffer show that the AgOx-NP sample have comparable oxygen on set and water oxidation activity ( Figure S1).…”
Section: Electro-generation Of Nano-particulate Type Silver-oxide Watmentioning
confidence: 99%